Developing Application Main Condensate Water System as a Learning Media - Narto, Amad; Sari, Ria Hermina; Fahrobi, Ilman Al (RSF Conference Series: Engineering and Technology, 2023)
An innovation of learning media through application is the answer to the learning challenges in the digitalization era as well as the impact of the COVID-19 pandemic. In this study, the main condensate water system is transformed into a learning media application for simulating the work process, distribution flow, and operation of the main condensate water system on board a ship. This study applied a research and development method using a five-stage research model known as “Mantap”. The study was started by conducting an initial study and followed by model development through designing the basic concept of the application. Validation and effectiveness assessments were then conducted to determine whether the application was valid and applicable enough as learning media. The study revealed that the application visualized using Adobe Animate is valid as a learning media. It gained a validity score of 3.25 from the visual design expert and 3.5 from the curriculum experts. Besides, the application was assessed to be effective as a learning media by receiving a validity score of 3.69 from the Marine Engineering students.